PENYULUHAN DAN PELATIHAN PENCEGAHAN MALARIA SERTA DETEKSI DINI MALARIA DAN ANEMIA DENGAN PEMERIKSAAN LABORATORIUM PADA PEKERJA PROYEK PENGHIJAUAN DI KECAMATAN ARANIO KABUPATEN BANJAR - Rifqoh, Rifqoh; Cahyono, Jujuk Anton; Kustiningsih, Yayuk (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2023)
Malaria remains a problem in Indonesia and in the world with morbidity and mortality rates quite high, caused by Anopheles mosquitoes which carry the Plasmodium sp parasite. Malaria has an impact on reducing hemoglobin levels in the blood which causes anemia. Forest workers are vulnerable to malaria and anemia. Lack of knowledge can be a factor in increasing the incidence of malaria and anemia. This community service activity aims to increase knowledge about malaria, improve malaria prevention attitudes and behavior, detect malaria and anemia in workers by laboratory examination. Implementation methods include counseling, questionnaires, observations, and laboratory examinations for malaria detection by Rapid Diagnostic Test (RDT) and Microscopic technique, Determine hemoglobin (Hb) levels using Point of Care Testing (POCT) method as an indicator of anemia in blood specimens of 50 forest workers in Aranio District. The results of this activity increased the knowledge, attitudes, and behavior of respondents regarding malaria prevention to 100%, malaria laboratory examinations both RDT and microscopic results were 100% negative. The Hb levels obtained ranged from 8.4 gr/dl to 15.2 g/dl which 35 respondents (70%) were normal and 15 respondents (30%) were below normal or anemia. Another outcome was the formation of the community group “Kelaan Block and Prevent Malaria Transmission“. It is recommended for further community service to continue with other programs based on the Healthy Village concept to prevent and maintain malaria elimination status in the Aranio area that supports the realization of health transformation in Indonesia. Keywords: Counseling, Knowledge, Malaria, Anemia, Forest Workers